THE EVALUATIVE INTONATION IN PORTUGUESE TEXTBOOKS ACTIVITIES IN ELEMENTARY SCHOOL - Santos Bezerra, Jane Cleide dos; Paixao, Sergio Vale da [UNESP]; Menegassi, Renilson Jose [UNESP] (Univ Estado Rio Grande Norte, 2019)
In this paper, we analyze how the concept of evaluative intonation is manifested in reading activities in the Portuguese didactic book in the present days. In emphasizing the role of intonation as an element that contributes to the construction of meaning of the utterance, we accept that this knowledge assists in the development of student-reader autonomy, since it is through reading that one constitutes an active transponder over things and the facts of the world in which he/she lives. Hence the option of using as a locus of this study, the Portuguese textbook, since this resource when using the discursive genres, allows the effectiveness of the nature of dialogical of language, since the use of text in teaching activities becomes the main requirement so that the discourses are constituted by the learner. The collections chosen for analysis were adopted in the city of Arapiraca (AL), in PNLD-LP / 2017. It is a documentary research, based on the studies of The Bakhtin Circle and as results we point out that intonation, as an axiological concept, is present in the textbook, explicitly and implicitly and that the understanding of its manifestation is a critical condition for the student to perform the tasks of constructing meanings in the reading process.
Keywords: Intonation; Portuguese textbook; Elementary School